Pengaruh Seminar Terhadap Self Efficacy Mahasiswa Universitas Negeri Malang - Prastiko, Mufti Nawang; Abdillah, Lucky Rafly; Trianjari, Novita; Pangesti, Teresma Trestia; Arifin, Imron; Ubaidillah, Aan Fardani (Proceedings Series of Educational Studies, 2024)
Abstract : Self-efficacy, which refers to an individual's belief in his or her ability to execute certain tasks, is a critical element in achieving academic success and student personal development. Malang State University, as a higher education institution committed to quality learning, is faced with the challenge of increasing student self-efficacy. One of the efforts taken is holding seminars as a means of developing students' skills, knowledge and self-confidence. The importance of understanding the influence of seminars on student self-efficacy at Malang State University underlies this research. This research aims to explore and explain the influence of seminar variables on self-efficacy. This research utilizes a quantitative approach with data collection methods in the form of questionnaire techniques. This research also has research results which can be concluded into 3 parts. First, students have a perspective or point of view that is included in very good qualifications regarding seminars. Second, students have a level of self-efficacy which is included in very good qualifications. Third, the seminar variable has an influence on student self-efficacy.Abstrak : Self-efficacy, yang merujuk pada keyakinan individu terhadap kemampuannya untuk mengeksekusi tugas-tugas tertentu, menjadi unsur kritis dalam mencapai keberhasilan akademis dan pengembangan pribadi mahasiswa. Universitas Negeri Malang sebagai lembaga pendidikan tinggi yang berkomitmen pada kualitas pembelajaran, dihadapkan pada tantangan untuk meningkatkan self-efficacy mahasiswa. Salah satu upaya yang diambil adalah penyelenggaraan seminar sebagai sarana untuk mengembangkan keterampilan, pengetahuan, dan keyakinan diri mahasiswa. Pentingnya pemahaman terkait pengaruh seminar terhadap self-efficacy mahasiswa di Universitas Negeri Malang mendasari penelitian ini. Penelitian ini mempunyai tujuan untuk mengeksplorasi dan menjelaskan pengaruh dari variabel seminar terhadap self efficacy. Penelitian ini memanfaatkan pendekatan kuantitatif dengan metode pengumpulan data berupa teknik kuesioner. Penelitian ini juga mempunyai hasil penelitian yang dapat disimpulkan menjadi 3 bagian. Pertama, mahasiswa mempunyai perspektif atau sudut pandang yang termasuk dalam kualifikasi sangat bagus mengenai seminar. Kedua, mahasiswa mempunyai tingkat self efficacy yang termasuk dalam kualifikasi sangat bagus. Ketiga, variabel seminar mempunyai pengaruh terhadap self efficacy mahasiswa.